Pengembangan Model Pembelajaran SIPAKAR sebagai Sistem Informasi Praktik Karya dan Refleksi untuk Pelacakan Progres Pembelajaran dan Penilaian Formatif Mahasiswa PPG Seni Budaya di Sekolah Mitra - Ike Ratnawati; Khusaini; Mitra Istiar Wardhana; Muslim; Ira Junita Suryantoro; Maria Goretti Indah Della Conseta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to develop the SIPAKAR (Practice and Reflection Information System) learning model as a digital system that supports learning progress tracking and formative assessment for Teacher Professional Education (PPG) Culture Arts students at partner schools. SIPAKAR is designed as an integrative platform that allows students to systematically document the practice of artworks and reflection activities, as well as allows lecturers and teachers to conduct formative assessments based on real-time data. The research approach used is the ADDIE development model, which at this stage is limited to the Development (D) stage, including the Analysis, Design, and Development stages of initial prototypes. The analysis stage includes a study of user needs, a study of PPG learning characteristics, and the identification of gaps in the existing documentation and assessment systems. At the design stage, the researcher developed a system structure that includes the features of paper uploads, rubric assessments, reflection journals, and learning progress tracking charts. The development phase resulted in a web-based prototype of SIPAKAR that was tested on a limited basis and received input from early users. Provisional results show that this model has the potential to improve clarity of learning outcomes, reflective student engagement, and accountability of lecturer and partner teacher assessments. This study recommends the integration of SIPAKAR into the technology-based PPG learning system in a broader and sustainable manner.